PEMBELAJARAN PENELITIAN TINDAKAN KELAS DI PERGURUAN TINGGI ISLAM - Mohamad Erihadiana (Jurnal Pendidikan Islam, 2013)
This study intends to develop a learning model of classroom action research (CAR) that can improve the ability of reasoning (logical and scientific) of the prospective teachers in one of the Islamic universities in Indonesia, in Faculty of Tarbiyah and Teacher Training UIN Sunan Gunung Djati Bandung. The approach used in this study was a Research and Development. The result of the experiement and its validation prove there is an increase in learning outcomes and the difference between the result of of the implementation of experimental model compared to that of the implementation of conventional learning model. The implementation still faces several problems such as: 1) Many lecturers of CAR courses do not fully understand the concept of CAR; 2) lecturers who are helped by assistants causes the discussion process is less comprehensive since the assistants lack of knowledge about the topic discuss; 3) Some lecturers rarely gave the report about the implementation observed; 4) students who attend a course CAR majority have never been taught and have not followed the Teaching Practice (PPL).